A Visible-Light-Driven Approach to Free Alcohol from Esters of Quinone Propionic Acid - Lu, Zheng; Xu, Yue; Wen, Ze; Xie, Changhong; Xie, Chengyue; Yu, Mengqian; Gao, Lingyun; Yang, Yong-Qing; Xu, Ximing (Synthesis, 2022)
Release of alcohol from quinone propionic esters (QPEs) propelled by visible-light is reported. 1°, 2°, and allylic alcohols could be freed from the corresponding QPEs under radiation from blue LED bulb in the presence of a photocatalyst. Ten examples are listed and the yields are good to excellent. Possible mechanism has been proposed and further applications of quinone propionic acid (QPA) in photochemistry would be expected.
Keywords: protective group; QPA; visible-light; photocatalyst; organo-reductant; Hantszch ester